Implementing Augmented Reality on a Multiple Floor Building as a Tool for Sales Product Knowledge - Arifitama, Budi; Syahputra, Ade (IJTB (International Journal of Technology And Business), 2017)
Research into indoor property floor plan associated with the use of augmented reality technologies is very limited. Most sales property developer used conventional ways on how they interact with potential client using brochure which lacks detailed information .This paper propose a solution that is capable of showing the actual size and form of the floor plan by visualizing into a 3d model to aid the salesman in explainig more accurately during meetingwith customers. We have applied a simple but effective ways to visualize a 3d floor plan compete with surrounding walls by using augmented reality. Result shown that by using augmented reality, salesman are easier to explain theproduct knowledge of the housing to the customer as every detailed information are stored in the software.